Anti-inflammatory and anti-oxidant mechanisms of an MMP-8 inhibitor in lipoteichoic acid-stimulated rat primary astrocytes: involvement of NF-κB, Nrf2, and PPAR-γ signaling pathways - Eun-Jung Lee; Jin-Sun Park; Yu-Young Lee; Do-Yeon Kim; Jihee Lee Kang; Hee-Sun Kim (Journal of Neuroinflammation, 2018)
Abstract Background Recent evidence suggests that reactive astrocytes play an important role in neuroinflammation and neurodegenerative diseases. Thus, controlling astrocyte reactivity has been suggested as a promising strategy for treating neurodegenerative diseases. In the present study, we investigated whether a matrix metalloproteinase (MMP)-8 inhibitor, M8I, could control neuroinflammation in lipoteichoic acid (LTA)-stimulated rat primary astrocytes. Methods The effects of M8I on the expression of inducible nitric oxide synthase, cytokines, and MMPs were examined in LTA-stimulated rat primary astrocytes by ELISA, RT-PCR, and Western blot analysis. The effects of M8I on reactive oxygen species (ROS) generation and phase II antioxidant enzyme expression were examined by the DCF-DA assay, RT-PCR, and Western blot analysis. The detailed molecular mechanisms underlying the anti-inflammatory and antioxidant effects of M8I were analyzed by the electrophoretic mobility shift assay, the reporter gene assay, Western blot, and RT-PCR analysis. Results Treatment with LTA, a major cell wall component of Gram-positive bacteria, led to astrocyte activation and induced the expression of inflammatory molecules such as iNOS, COX-2, and pro-inflammatory cytokines. In addition, LTA induced the expression of MMPs such as MMP-1, MMP-3, MMP-8, MMP-9, and MMP-13 in rat primary astrocytes. Based on previous reports showing that MMP-8 plays a role as a proinflammatory mediator in microglia, we investigated whether MMP-8 is also involved in inflammatory reactions of reactive astrocytes. We found that treatment of astrocytes with M8I significantly inhibited LTA-induced expression of iNOS, TNF-α, IL-1β, IL-6, and TLR-2. In addition, M8I inhibited LTA-induced NF-κB, MAP kinase, and Akt activities, while it increased the anti-inflammatory PPAR-γ activities. Moreover, M8I showed antioxidant effects by suppressing ROS production in LTA- or H2O2-stimulated astrocytes. Interestingly, M8I increased the expression of phase II antioxidant enzymes such as hemeoxygenase-1, NQO1, catalase, and MnSOD by modulating the Nrf2/ARE signaling pathway. Conclusions The data collectively suggest the therapeutic potential of an MMP-8 inhibitor in neuroinflammatory disorders that are associated with astrocyte reactivity.